The Impact of Hikayat Prang Sabi on the Community: A Sociology of Literature Study - Chalis, Nur; Syarifuddin, Achmad; Nuruddin, Nuruddin; Sarip, Mohamad; Suraiya, Suraiya; Zulhelmi, Anshar; Safri, T. Mulkan (Jurnal Ilmiah Peuradeun, 2024)
The growing fighting spirit of the Acehnese people against the Dutch colonialists has been documented in history. One factor that significantly influenced this heroic spirit was the Hikayat Prang Sabi (The letter literature of war). How did this text shape the courageous spirit of the Acehnese in their resistance against the invaders? This paper examines the influence of Hikayat Prang Sabi (HPS) on its readers and the broader community. This study aims to reveal the impact of Hikayat Prang Sabi on Acehnese society. The theoretical framework used is the sociology of literature, focusing on the relationship between author, the literary work, and the reading public. The methodology employed is a descriptive qualitative approach that draws on literary sociology. The results indicate that HPS was a significant literary work that deeply affected its readers, especially the Acehnese who embraced it. The creation of HPS by Tgk. Chik Pante Kulu was closely tied to the political conditions in Aceh at the time, as the region was engaged in conflict with Dutch military force. During the Aceh-Dutch war, HPS was read before going to battle until it was confiscated and destroyed by the Dutch. Even after the war, HPS remained a crucial reference for the Acehnese in rebuilding political power.